An antimonate pyrochlore (H1.23Sr0.45SbO3.48) for photocatalytic oxidation of benzene: effective oxygen usage and excellent activity. Issue 3 (22nd December 2016) - Chen, Jing; Shao, Yu; Li, Danzhen
Abstract : The effective adsorption of oxygen molecules makes the antimonate pyrochlore sample (H1.23 Sr0.45 SbO3.48 ) an excellent photocatalyst. Abstract : The sample H1.23 Sr0.45 SbO3.48 crystallized in a pyrochlore structure is applied to photocatalytic oxidation of benzene in the gaseous phase. The pyrochlore structure is considered as the key factor for the effective oxygen adsorption, which makes the sample exhibit excellent photocatalytic activity.